Development of Job Satisfaction Measurement Tool in Teleworking Work Arrangement (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Flexible work settings using connection-based and technological devices, commonly referred to as teleworking, have become increasingly prevalent since the COVID-19 pandemic. This change in work settings may affect various aspects of job satisfaction among employees, necessitating adjustments in measuring employee job satisfaction. This study aims to develop a measurement instrument for job satisfaction within the context of teleworking, knowns as the Work Engagement Scale (WES). The development of the WES measurement instrument is based on the nine dimensions of job satisfaction proposed by Spector (1985). The participants in this research were 146 workers who had been teleworking for at least one year in private companies, government institutions, state-owned enterprises, or nonprofit organizations. The result of realibility testing indicate that the WES measurement instrument, both overall and in its six dimensions, demonstrated high internal consistency. Construct validity testing shows that WES measurement instrument, both overall and in each dimension, is valid for measuring job satisfaction. Furthermore, the items in the Job Satisfaction measurement instrument, both per dimension and overall, exhibited good discrimination and were evenly distributed. Overall, the psychometric testing results of the WES measurement instrument suggest that it has the potential to effectively measure job satisfacton among employees using teleworking system.